Conjunto de dados de annealing aplicados a Termocronologia por traços de fissão em Zircão: estudo de caso de uma amostra brasileira - Sales, Antonio Said Webbe (2021)
Fission Track Thermochronology (TTF) has been used for decades as a technique that makes it possible to date and infer the thermal history of rocks in regions of geological interest, from different minerals. The methodology is based on the study of fission tracks spontaneously generated by 238U or induced in a nuclear reactor by 235U, which after a chemical attack can be observed under an optical microscope. Specifically, this project focused on the study of the zircon mineral, which is a mineral that is very abundant in nature and that contains about dozens of ppm of uranium in its chemical composition. Therefore, it can be used as a thermochronometer in the TTF, where the density and length of the fission tracks in the mineral are useful for dating and inferring the thermal history of the rocks present on the Earth's surface. This is because the temperature to which this mineral has been exposed for millions of years causes the fission tracks to shorten. This phenomenon is known as annealing and can be better understood from kinetic models, known as annealing models. Such models use a data set that shows how the phenomenon interferes with fission tracks. The data set available for the calibration of TTF systems using NST zircon is extracted from a region that has a thermal history defined by a rapid cooling and the absence of a subsequent geological heating, being its dating from the Miocene geological era (~ 22 Ma). Therefore, the objective of this work is to obtain a new set of annealing data with zircons obtained from a region with a thermal history and geological era different from the NST zircon. For this, a sample of Poços de Caldas-MG was chosen, called ZPC whose dating back to the Mesozoic era (~ 80 Ma). Two aliquots were prepared: one containing only spontaneous fission traces (238U) and the other with only induced fission tracks (235U). Both aliquots were subjected to heating experiments for 1, 10 and 100 hours at a temperature between 500 and 800 ° C. The results showed the fission traces of the ZPC sample have behavior compatible with those of the sample commonly used by the scientific community. The new set of annealing data from the Brazilian sample was applied to annealing models and has potential as a data source for reconstructing thermal histories in regions of geological interest.